Study of the name structure of Ngara Waje Sabu tribal society - Olivia de Haviland Basoeki; Lusia Eni Puspandari (English, 2018)
This paper specifically examines the study of Ngara Waje structure in Sabu culture, with coverage (1) the lingual structure of the self-name; (2) The meaning of the name of Ngara Waje according to the perception of the Sabu people. The results of the analysis obtained the format of honorific name Ma / Na + ngara Waje + ngara Hawu. The emphasis in the Waje wajang name structure kajan in the name of the Sabu is not distinguished by sex but is characterized by Ama (Ma's abbreviation) for men and Ina (Na) for women. The lingual arrangement of names in Sabu culture has special characteristics ie the name of the Sabu always terminated vowels (a, i, u, e, o). The name of the Sabu person does not end in dead or consonant at the end of the word, such as Hae, Djara, Lodo, Nguru ,. Second, there are no different double consonant together, but the consonant immobilization must be the same, for example: Wannyi, Banni, Lappa. The third characteristic, does not recognize the characters c, f, q, s, v, x, and z because the people of Sabu do not recognize these characters so they cannot pronounce the capital letters. Example: they are difficult to articulate a word that has a phoneme / s / like the word Savu pronounced into Hawu; the school is pronounced school; Frans is pronounced Para, Simon is pronounced Himo. Waje ngara name in Sabu culture, has certain characteristics of meaning, namely the meaning of hope, the meaning of memories and the meaning of flattery. In addition, Waje's meaning is also associated with certain aspects such as objects around (humans, animals, plants, other objects), cosmic objects (sun, moon, stars) and natural elements (fire, water, earth, mountains).